Silk road diplomacy: Geopolitics and histories of connectivity. Issue 7 (9th November 2020) - Winter, Tim
ABSTRACT: The Silk Road has become one of the key geocultural and geostrategic concepts of the twenty-first century. Identified by two routes – maritime and overland, the Silk Road stretches across the Indian Ocean and Eurasian landmass; regions that will be of paramount importance in an increasingly multi-polar world. Through Belt and Road, China proclaims to be 'reviving' the Silk Road for the twenty-first century; ambitions that are creating forms of diplomacy across multiple sectors and countries. To contextualise such developments, this paper examines the Silk Road's historical formation as an arena of diplomacy and international cooperation. It argues that this stylised, romanticised depiction of pre-modern globalisation came to be associated with peace and harmony, cosmopolitanism and inter-cultural dialogue after World War II. Within this, however, Silk Road diplomacy has served as a vehicle for nationalist and geopolitical ambitions. The paper argues such entanglements underpin China's Belt and Road Initiative today.